Dinâmica do transporte sobre trilhos na região metropolitana de São Paulo - RMSP - desenvolvimento, problemas e diretrizes - Ribeiro, Bruno (2019)
The city of São Paulo and the development of its Metropolitan Region, are closely linked to the history of the railroad. The rail system was implemented and built to meet the demands of cargo transportation, mainly from the Port of Santos to the city and the region of Plateau and vice versa, while the passenger flows were very concentrated in time and space in pendular model. The implantation of the railway lines and their stop stations, converged the metropolization of São Paulo. The stations generated centralities in their localities. The analysis of the physical structure of the urban environment, guided by the high capacity transport and its centralities, has in the identification of the potentialities of the railway system in integrating urban equipment and promoting economic and sustainable development. The RMSP is a huge economic center, notably housing many tertiary activities, which have quite different transport demands from the industries. The great change between the industrial stage and the current pre-eminent tertiary is the accumulation of functions in the city of São Paulo. The travel generated by work and consumption, greatly increased the demand for passenger transportation between housing areas and areas of concentration of labor and services. The analysis of the lines and the stations of the transport system on passenger tracks (CPTM and Metrô), resulted in the evaluation of the potentialities, where the lines that make up the Metropolitan Transportation System of São Paulo, form axes that interconnect the entire RMSP, and together with its stop stations and intermodal terminals, offer its users infrastructure beyond the transport of passengers. From this understanding, the proposals turn to short- and medium-term actions, where the requalification of existing structures, not only promote the displacement, but also access to culture and leisure, contributing to the valuation of intangible assets. It can be seen that the rail transportation system represents a centralizing pole through the case study - the Corinthians Itaquera Intermodal Station, and demonstrates the importance it exerts on the region, the local population, as well as other users of the transportation system.